Word and Pseudoword Superiority Effects in a Shallow Orthography Language: The Role of Hemispheric Lateralization. Issue 2 (April 2014) - Ripamonti, Enrico; Traficante, Daniela; Crippa, Franca; Luzzatti, Claudio
The word superiority effect (WSE) has made it possible to demonstrate the automatic activation of lexical-orthographic entries in reading. The observation of this effect is important since it led to experimental support of the main cognitive reading models. These models were mostly developed on English data, hence the verification in different orthography systems is relevant. The present study tested WSE in Italian, a language in which this effect was predicted to be less constant given the highly consistent correspondence between orthography and phonology. Moreover, the presentation of the items in a lateralized visual field condition allowed testing of assumptions about the roles of the right and left hemispheres in written word recognition and, in particular, on the hemispheric lateralization of lexical processing. Two experiments were conducted with undergraduate students who had to recognize a target letter within a word, pseudoword, or nonword. In Experiment 1, prime and probe letters were in the same letter case, while in Experiment 2 they were in different letter cases. Error rates and reaction times were analyzed with mixed models. The results showed a superiority of pseudowords (pseudoword superiority effect; PSE) over illegal strings with no evidence of a clear superiority of words over pseudowords for both left and right visual field presentations. This suggests that in Italian, the sub-lexical route could play a major role in reading and that this route relies on a visual-perceptual orthographic coding concerning familiarity of letter combinations, which is also available to the right hemisphere.